2013
DOI: 10.4054/demres.2013.29.26
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal malnutrition and subsequent foetal loss risk: Evidence from the 1959-1961 Chinese famine

Abstract: BACKGROUNDScientists disagree on whether prenatal malnutrition has long-term influences on women's reproductive function, and empirical evidence of such long-term effects remains limited and inconsistent. METHODSUsing the retrospective pregnancy history of 12,567 Chinese women collected in a nationally representative sample survey in 2001, this study conducted difference-indifferences analyses to investigate the relationship between prenatal exposure to the 1959-1961 Great Leap Forward Famine in China and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
2
3
1
Order By: Relevance
“…In other words, we do not believe that prenatal exposure to famine could “causally” decrease one’s health risks in later life. Instead, we concur with Song and colleagues that because fetuses, infants, children, and adults of poorer health endowment are more likely to be lost in the famine, the surviving famine cohort are likely to consist of the fittest individuals who are resilient to adverse environments (Song, 2009, 2010, 2013b; Song et al, 2009). Therefore, it is only possible to observe the negative long-term health effects of famine when famine survivors are not dominated by the selective frailty process.…”
Section: Discussionsupporting
confidence: 84%
“…In other words, we do not believe that prenatal exposure to famine could “causally” decrease one’s health risks in later life. Instead, we concur with Song and colleagues that because fetuses, infants, children, and adults of poorer health endowment are more likely to be lost in the famine, the surviving famine cohort are likely to consist of the fittest individuals who are resilient to adverse environments (Song, 2009, 2010, 2013b; Song et al, 2009). Therefore, it is only possible to observe the negative long-term health effects of famine when famine survivors are not dominated by the selective frailty process.…”
Section: Discussionsupporting
confidence: 84%
“…In rural areas, famine exposures in both prenatal period and infancy period were significantly correlated with stillbirth in later life, whereas in urban areas, the increased risk of stillbirth was found only in the infancy exposure group. This is not in accordance with a previous study that only observed the famine effect on stillbirth in urban areas rather than rural areas . Different sample sizes, regional distribution, classification of exposure, and intensity of famine in study areas could explain this inconsistency.…”
Section: Discussioncontrasting
confidence: 98%
“…In this study, females who experienced famine in their early life showed a higher potential incidence rate ratio of stillbirth in adulthood compared with their unexposed counterparts, whereas no association was found between famine exposure and spontaneous abortion. The result was consistent with some previous studies . The divergent famine effects on the two reproductive outcomes were likely explained by different biological mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…First, two hospital-based investigations were regional because they only based on one psychiatric hospital records separately. Second, the estimation of SCD has methodological deficiencies since it cannot exclude intrinsic cohort differences other than famine; that is, the observed differences across birth cohorts may be a reflection of general cohort effects even without exposure to famine [15, 16]. A valid strategy to more robust capture the famine effect on health outcomes relies on difference-in-difference (DID) models, established by examining the regional variations of famine exposure across birth cohorts [17, 18].…”
Section: Introductionmentioning
confidence: 99%